Parental Emotional Reinforcement-Demands, and the Intrinsic Motivation of Santri in Qur’anic Memorization: A Study in Indonesian Islamic Boarding Schools - Taufikin, Taufikin; Nurhayati, Sri; Majeed, Jahangeer; Afzal, Muhammad; Al-Badawi, Habib; Chibani Mansouri, Mabrouk; Fatma, Gulnaz (Universitas Muhammadiyah Surakarta, 2025)
In Indonesia, early Qur'anic memorization is a culturally and spiritually significant practice, particularly within Islamic boarding schools (pesantren). Despite its importance, limited research has examined how parent-child dynamics influence children's motivation in this context. This study investigates the motivational experiences of children aged 6 to 12 engaged in Qur’anic memorization, with particular attention to the role of parental emotional reinforcement, directive expectations, and intrinsic spiritual aspirations. A qualitative, psycho-hermeneutic approach was employed, involving interviews with one kiai, 20 ustaz-ustazah, and 23 santri who had memorized 30 Juz of the Qur’an, complemented by observations of 540 students and analysis of their monthly memorization progress reports. Findings reveal three distinct motivational trajectories: (1) extrinsic motivation through parental emotional reinforcement (e.g., praise, rewards), (2) passive compliance under parental demands, and (3) intrinsic motivation grounded in the child's spiritual calling. While extrinsic motivation often initiates engagement, intrinsic motivation is crucial for sustaining long-term memorization commitment and internalizing religious values. This study enriches theoretical understanding of motivation in Islamic education by integrating Self-Determination Theory and hermeneutic analysis. It also offers practical implications for parents, educators, and policymakers seeking to foster supportive and autonomy-enhancing environments in pesantren settings. Further research is recommended to explore how sociocultural structures and pesantren pedagogies influence the development of religious motivation among young learners.